USE OF PUPILLOMETRY IN THE DIAGNOSIS OF STRESS IN PIGLETS TRANSPORTED IN A TROPICAL CLIMATE - Machado,Nítalo A. F. (2021)
ABSTRACT The objective of this study was to evaluate the reactivity of the pupillary area (PA) as a non-invasive method for diagnosing stress in piglets submitted to transport. A total of 10 journeys were monitored and grouped according to the transport distance (15 and 75 km). Were sampled 360 piglets (25±3.8 kg) to measure the PA, body temperature (BT), and serum concentrations of cortisol and creatine kinase (CK). The micrometeorological characterization of the load was performed using enthalpy comfort index (ECI). It was possible to identify an increase of 19.32% (+18.91 mm2; P< 0.001) in PA of piglets transported in shorter journeys (15 km), as well as the highest mean values of BT (+ 1.24 °C; P< 0.001), cortisol (+ 2.37 ng/mL; P< 0.001) and CK (+ 379 U/L; P= 0.025). In this study, high correlations of PA were observed with r = 0.922, 0.900, 0.842 and 0.829 ( P< 0.05) for cortisol and CK, BT and ECI of trailer, respectively. In conclusion, we state that PA reactivity is a physiological response for the diagnosis of stress of piglets transported. Further research will refine this technique in order to make this non-invasive acquisition method more practical and adaptable to different transport conditions.